Development of a Migraine Trigger Measurement System Using Surprisal - Dana P. Turner; Emily Caplis; Twinkle Patel; Timothy T. Houle (Neurology Research International)
Conclusions: These findings reinforce the utility of surprisal measures for capturing nuanced patterns in the vast array of headache trigger data and support their potential as a measurement tool for understanding trigger exposures.